Peran Mahasiswa KKM dalam Meningkatkan Perilaku Hidup Bersih dan Sehat di SD Negeri Bayak - Ummy Kalsum; Agustina Dwiyanti; Siti Ulpah; Evi Nuraeni (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
To improve public health, especially for elementary school-aged children, one of the most important prevention methods is Clean and Healthy Living Behavior (PHBS). The purpose of this study was to improve the understanding and utilization of PHBS among students at Bayak Public Elementary School in Siremen Village, Tanara District through counseling and live demonstrations. This activity was carried out by the KKM Group 95 team from Bina Bangsa University for 83 second- and fourth-grade students at Bayak Public Elementary School. The method used was a participatory educational approach, namely by providing counseling related to PHBS and continued with live demonstrations of handwashing, tooth brushing, and maintaining personal hygiene. The material was delivered interactively to make it easier for children to understand, including the use of visual media such as posters and pictures. The students were also given direct practice tools such as soap, toothbrushes, and toothpaste so they could directly practice proper hygiene practices. The results of the activity showed that students had a better understanding of PHBS and made positive changes in their daily lives at school. It appeared that students were better trained in maintaining personal and environmental hygiene. They also began to get used to washing their hands before eating, maintaining dental hygiene, and disposing of trash properly. Teachers and homeroom teachers also actively supported this initiative by participating in outreach activities and monitoring changes in student behavior. This initiative not only raised students' awareness of the importance of health but also encouraged active school participation in creating a healthy learning environment. It is hoped that this initiative will serve as a reference for schools in teaching students how to live a healthy and clean lifestyle in a sustainable manner.